Modeling of Air-Water Filled Rubber Dam Under Hydrostatic Conditions - Qusay Khaleel; Thair Khayyun; Khudhayer Abdullah (Engineering and Technology Journal, 2021)
Inflatable dams, also called rubber dams, are flexible cylindrical inflatable and deflatable structures attached to a rigid base; these dams are basically cylindrical tubes made of rubberized material and inflated by air, water, or a combination of the two. In this paper, the air/water inflatable dam was studied and analyzed numerically using ANSYS software. The 3-parameter Mooney-Rivlin Model was used to model the rubber material of the dam. At first, a physical model from literature was used to calibrate the results of the ANSYS software, and then a new model was analyzed with different dimensions and conditions. Thirty-six simulations were made using the ANSYS software to calibrate the software, based on experimental results from the literature. The simulations achieved a very low error rate compared to the experimental findings, with a maximum error rate of 1.45 percent. After that, a new air/water-filled dam model simulation was carried out. The new inflatable dam was analyzed with large dimensions that can be used to reserve water at high elevations. Several water heights (2, 4, 6, 8, and 10 m) were used as input at the upstream of the dam, and their effect on the dam body was verified on the assumption that there was no water downstream of the dam for all simulations. The height of the used inflatable dam was assumed to be 11 meters (first 5.5 m water pressure and the second 5.5m different air pressure values), and the bottom gaskets was 9.7 meters wide. It is evident from the analysis that the upstream water appears to push the dam to the right side (towards downstream), causing a change in dam equilibrium shape. The difference in the cross-sectional equilibrium profile of the dam is due to the change in air and water pressures on the element. Thus, it changes the tension and slope of the dam membrane elements. The simulation results showed that the membrane tension increases as the upstream head increases, and as the internal pressure increases, the tension increases. This rise in tension as the upstream head rises may be due to the rise in the forces on the element, and hence the membrane tension increases.